2014
DOI: 10.1001/jamaophthalmol.2014.1093
|View full text |Cite
|
Sign up to set email alerts
|

Management of Functional Epiphora in Patients With an Anatomically Patent Dacryocystorhinostomy

Abstract: IMPORTANCE Approximately 5% to 10% of patients continue to experience persistent epiphora following an anatomically successful dacryocystorhinostomy (DCR) for nasolacrimal duct obstruction or stenosis. OBJECTIVE To investigate the management and success rate of so-called "functional failure" of DCR for nasolacrimal duct obstruction by experienced lacrimal surgeons. DESIGN, SETTING, AND PARTICIPANTS Multicenter retrospective case series including 5 Australian and New Zealand centers. Participants included 61 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 17 publications
0
42
1
3
Order By: Relevance
“…This discrepancy between anatomical and symptomatic success after DCR is referred to as 'functional failure'. 6,7 The ultimate purpose of DCR is the resolution of tearing symptom; therefore, the functional aspect must be emphasized when analyzing surgical outcomes. However, the causes or risk factors for functional failure remain largely undetermined, and an adequate management strategy has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy between anatomical and symptomatic success after DCR is referred to as 'functional failure'. 6,7 The ultimate purpose of DCR is the resolution of tearing symptom; therefore, the functional aspect must be emphasized when analyzing surgical outcomes. However, the causes or risk factors for functional failure remain largely undetermined, and an adequate management strategy has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…In different study series, the frequency of recurrent epiphora after DCR surgery is reported as 5% to 17% [ 17 , 18 ]. The most important factors that play a role in the failure of a DCR surgery are inadequate rhinostomy, excessive scar tissue proliferation, anatomic anomalies and concomitant paranasal sinus infections [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its Success rate ranges from 80 to 90% according to different patient's and surgeon's factors. 3,[5][6][7][8][9] nonetheless, and given its invasive and lengthy nature, external DCR has its own drawbacks. Intraoperative complications, such as extensive bleeding, aren't infrequent.…”
Section: Introductionmentioning
confidence: 99%